Association of lncRNA CCAT2 and CASC8 Gene Polymorphisms with Hepatocellular Carcinoma - Wu, Edie-Rosmin (Int J Environ Res Public Health, 2019)
The worldwide incidence of hepatocellular carcinoma (HCC), the major histological type of primary liver cancer, is heterogeneous due to the variable prevalence of etiological factors, indicating a correlation of HCC risk with genetic variations among individuals. Among long non-coding RNAs (lncRNAs) located in the chromosome 8q24 loci and involved in the carcinogenesis are colon cancer associated transcript 2 (CCAT2) and cancer susceptibility candidate 8 (CASC8). In this study, the association of CCAT2 and CASC8 gene polymorphisms with the occurrence of HCC was explored between 397 HCC patients and 1195 controls. We found that carriers of rs6983267 GG in CCAT2 were more susceptible to HCC, with the odds ratio (OR) and adjusted odds ratio (AOR) being 1.532 (95% CI, 1.103–2.129; p = 0.011) and 1.627 (95% CI, 1.120–2.265; p = 0.033), respectively. Moreover, for patients stratified by age (under 65), gender (male only), or status of drinking (habitual drinkers), a protective effect of CASC8 rs3843549 on presenting high Child–Pugh scores, metastatic vascular invasion, or large-size tumors was observed in a dominant model. Collectively, our data reveal association of CCAT2 and CASC8 gene polymorphisms with the occurrence and progression of HCC.